The effect of traditional Chinese medicine on renal function: A longitudinal cohort study with findings from 2011 to 2015 CHARLS - Li, Wei; Sun, Ning; Gamber, Michelle; Chen, Maxwell J.; Sun, Wenjie (Medicine (Baltimore), 2025)
Current treatment methods for kidney disease are limited. Traditional Chinese Medicine (TCM) is proposed as an alternative therapy to treat those patients with kidney disease in China though the toxicities of TCM remain unclear. The estimated glomerular filtration rate (eGFR) is used to reflect kidney function and determine kidney disease stages. This study aims to examine the effect of TCM on eGFR among middle-aged Chinese. Data were drawn from 3 waves (2011-2015) of the China Health and Retirement Longitudinal Study for a secondary analysis involving Chinese adults aged 45 and older. TCM was categorized into 3 levels: never, moderate, and heavy use. Generalized linear mixed models were used to estimate the effect of TCM use on eGFR, adjusting for covariates and stratifying by baseline self-reported kidney disease. Among 5944 individuals, the proportions of never, moderate, and heavy TCM users were 63.1%, 26.0%, and 10.9%, respectively. Overall, TCM use was significantly associated with impaired renal function at baseline, and the association was consistent among those without kidney disease. Lower eGFR was associated with increased TCM usage (moderate: Beta: −0.77 [95% CI: −1.45, −0.10], and heavy: −0.84 [−1.79, 0.11]). eGFR decreased slower among heavy users compared to the never group (1.40 [0.36, 2.44]). TCM use is associated with impaired renal function among Chinese elderly. Further research is needed to better understand the mechanisms behind the complicated relationship between TCM use and renal function.